Development of China Light-Duty Vehicle Test Cycle - Liu, Yu; Wu, Zhi Xin; Zhou, Hua; Zheng, Han; Yu, Nan; An, Xiao Pan; Li, Jing Yuan; Li, Meng Liang (International journal of automotive technology, 2020)
Driving cycles provide a basis for vehicle development and calibration and also serves as the foundation for energy consumption and emissions certification of vehicles. This paper presents the China Light-Duty Vehicle Test Cycle (CLTC) developed by the China Automotive Technology & Research Center (CATARC). First, the important steps and technical routes toward the CLTC development process are summarized. Second, the specific CLTC development process is presented in detail, including the data acquisition and data analysis procedures, weighting factor development and driving cycle construction. Then, the main driving characteristics of the New European Driving Cycle (NEDC), the Worldwide Harmonized Light-Duty Vehicles Test Cycle (WLTC), the Federal Test Procedure (FTP-75), the CLTC and the actual collected data are compared. The CLTC has low average speed, a high idle speed ratio and more frequent acceleration and deceleration characteristics. Finally, 70 vehicles are tested based on the NEDC, WLTC, and CLTC according to their legislative procedures in the vehicle emission laboratories of the CATARC and the manufacturers. The results show that the CLTC’s fuel consumption is much higher than that of the NEDC and WLTC, and CLTC can effectively reflect the actual fuel consumption of users.